The fields of Fitrah: analytical study in the light of Holy Quran - Muhanna, Hanadi Issa (Journal of Humanities & Social Sciences, 2019)
This Research aims to study the fields of Fitrah in the Holy Quran. The researcher used qualitative research methodology, the researcher concluded the following results: Quran indicates that the whole universe and all creatures are a field of Fitrah, whether Visible or invisible, which can be classified into the fields of general systems of Fitrah and the specialized systems of Fitrah, The research concluded that there is a relationship between general and specialized systems in the fields of Fitrah The researcher recommended conducting further studies on Fitrah ,and Inclusion of Fitrah as a subject of psychological, social, religious and natural Research Centers.
Keywords: The Holy Quran; fields of instinct